A theoretical method for estimating the torque of the shearer drum and the verification by full-scale shearer cutting experiments. (August 2022) - Li, Xuefeng; Wang, Shibo
Highlights: Probability density distribution of cutting force follows the normal distribution. Cutting space in relieved cutting is considered in pick cutting force estimation. Instantaneous pick cutting force is estimated during rotary cutting. Full-scale shearer cutting tests are conducted to verify the theoretical model. Abstract: As the drum consumes 80 ∼ 90% of the power of the shearer, the torque of the shearer drum is an important parameter in designing shearers. A theoretical method for estimating the torque of shearer drum is proposed considering not only the kinematic parameters of shearer, but also the structural parameters of shearer drum and the arrangement of picks. The probability density distribution (PDD) of cutting force and the effect of tool spacing on cutting force were obtained by full scale cutting tests. And then, the instantaneous cutting force of the pick is reconstructed based on the calculation of the instantaneous cutting depth during shearer drum rotating. The drum torque is obtained by superposing the cutting forces of all picks considering the structure of shearer drum. This model performed well in estimating the mean value of drum torque by comparison with the results of full-scale shearer drum cutting experiments.